Combinatorial non-covalent assembly of graphene oxide and chromophores into hybrid nanofilms for organic electronics. (16th January 2023) - Gusarova, Elizaveta A.; Zvyagina, Alexandra I.; Aleksandrov, Alexey E.; Averin, Alexey A.; Tameev, Alexey R.; Kalinina, Maria A.
Abstract : Functionally different 2D hybrids were assembled by using the same starting set of components comprising graphene oxide, perylene chromophore, polydiacetylene surfactant and divalent ions to modulate the properties of resulting systems. Abstract : A combinatorial method was applied for fabricating functionally different 2D hybrids by using the same starting set of components comprising graphene oxide, perylene chromophore, polydiacetylene surfactant and the salts of divalent ions (Ni(ii ), Co(ii ) and Zn(ii )) to modulate the properties of resulting systems. The components were assembled through either hydrogen or coordination bonding into layered nanofilms with a thickness 8–20 nm to integrate them into conventional ITO-based cells. Depending on their composition, the hybrids provide different operational characteristics to the resulting devices. The combination of graphene oxide with the light-absorbing polymer exhibits photovoltaic properties, whereas the adding of nickel ions transforms the hybrid into the monopolar conductive layers. The combination of two chromophores gives a multipurpose nanoelement, which performs as either non-linear resistor, diode or photodiode. This strategy can be easily applied to other combinations of chemicals for creating various hybrid nanofilms with targeted functional properties for organic electronics.